Neonatal Outcomes Based on Duration of Exposure to Antenatal Corticosteroids in Indicated Preterm Deliveries - Cawyer, Chase R.; Kuper, Spencer G.; Dimperio, Lisa A.; Tita, Alan T.; Biggio, Joseph R.; Harper, Lorie M. (American Journal of Perinatology, 2019)
Objective To evaluate how duration of exposure to antenatal corticosteroids (ACSs) prior to delivery affects neonatal outcomes in indicated preterm deliveries.Study Design This is a retrospective cohort of all indicated singleton preterm deliveries (23–34 weeks) in a single tertiary center from 2011 to 2014 comparing those who received ACS 2 to 7 days versus >7 days prior to delivery. The primary neonatal outcome was a composite of arterial cord pH < 7 or base excess ≤ 12, 5-minute Apgar ≤ 3, cardiopulmonary resuscitation, culture-proven neonatal sepsis, intraventricular hemorrhage grade III/IV, necrotizing enterocolitis, and neonatal death. Analyses were stratified by delivering gestational age (230/7–276/7, 280/7–316/7, and 320/7–336/7 weeks). Multivariate logistic regression refined point estimates and adjusted for confounders.Results In total, 301 women delivered >48 hours after initial ACS dose, 230 delivered within 2 to 7 days, and 71 delivered >7 days. Infants with an interval of >7 days had no significant increase in the unadjusted composite neonatal outcome (p = 0.42), but when adjusted, the composite neonatal outcome (adjusted odds ratio [AOR]: 2.7; 95% confidence interval [CI]: 1.18–6.31) and neonatal death (AOR: 4.20; 95% CI: 1.39–12.69) were significantly increased with an ACS interval of >7 day.Conclusion In this cohort, the benefit of ACS diminished >7 days after administration, particularly when delivery occurred at <32 weeks.
Keywords: corticosteroids; neonatal death; periviable birth; indicated preterm delivery